Nitrate, nitrite and microbial denitrification in drinking water from Ozun village (Covasna County, Romania) and the association between changes during water storage - Orsolya-Csilla RÁDULY; Anca FARKAS (Studia Universitatis Babeș-Bolyai. Biologia)
Severe groundwater contamination affects drinking water quality in many vulnerable zones across Romania. Ingestion of high levels of nitrate and nitrite can lead to the emergence of compounds with major toxicological effects. The present study was aimed to assess nitrate and nitrite concentrations in parallel with the activity of denitrifying bacteria, in different groundwater sources from Ozun village, Covasna County. Natural denitrification potential based on local microbiota was investigated during water storage for one month. Results indicate that tap water supplied from the public system complies with drinking water criteria, but most domestic wells are not safe. Nitrate concentrations exceeded the maximum limit allowed for drinking water in most of the samples collected from dug wells, while nitrite ions occurred within the mandatory limit. Denitrifying bacteria were detected in all groundwater samples, with the exception of one well. Regrowth of denitrifying bacteria was observed during water storage, but significant reduction of nitrate, nitrite or their sum of ratio did not occurred as a general rule. The association between percentage changes in bacterial counts, nitrate and nitrite concentrations was not statistically significant. In conclusion, enhancing the bioremediation potential of local microbiota by groundwater storage at household level is not an efficient strategy for nitrate/ nitrite removal.